From Users to Custodians : Changing Relations between People and the State in Forest Management in Tanzania - Wily, Liz Alden; Dewees, Peter A. (World Bank, Washington, DC, 2014)
Central control of forests takes management responsibility away from the communities most dependent on them, inevitably resulting in tensions. Like many African countries, Tanzania--which has forest or woodland cover over 30-40 percent of its land--established central forestry institutions at a time when there was little need for active management and protection because population pressures were low. But in the face of scarce public resources and burgeoning demand from the growing population for agricultural landand woodland products, there has been growing recognition of the need to bring individuals, local groups, and communities into the policy, planning, and management process if woodlands are to remain productive in the coming decades. Tanzania established its first three community-owned and -managed forest reserves in September 1994. Today, supported by substantive policy reforms that largely grew out of the early experiences with community-based management, more than 500 villages own and manage forest reserves, and anoher 500 or so smaller social units and individuals have recognized reserves. Joint management by the state and the people is getting underway in at least four government-owned forest reserves.The authors describe the evolution of community-based forest and woodland management in Tanzania and the underlying policy, legal, and institutional framework. They draw together some of the lessons from this experience and review emerging issues. They find that the most successful initiatives involving communities and individuals have been those that moved away from a user-centric approach (like that often used in South Asia) and toward an approach based on the idea that communities can be most effective when they are fully involved in all aspects of decisionmaking about management and protection. This suggests that the government should allow communities to become engaged as managers in their own right, rather than as passive participants who merely agree to the management parameters defined by the government. The Tanzanian experience has shown that community-based forest and woodland management can be an integral part of initiatives that seek to improve governance over natural resources by improving accountability and by democratizing decisionmaking at the local level.